“ESPIE”: possibilidades de inovação pedagógica a partir da exploração de Objetos Digitais de Aprendizagem - Varela, Eloisa Marques Cardoso (Universidade do Vale do Rio dos Sinos, 2024)
We live in a knowledge society, in which many students are different from those who passed through school not so long ago. Education must change to keep up with the changing profile of these students. Within this context, this research aims to identify and analyze ways of enhancing the use of the ESPIE platform, as a repository of Digital Learning Objects in classroom teaching and as a strategy for strengthening pedagogical innovation. To achieve the proposed objective, a qualitative methodological approach was selected, based on a single case study. Data has been collected through document analysis, an online questionnaire and a semi-structured interview. Bardin's (2011) Content Analysis technique was used to process and analyze the data. The results of this movement make it clear that innovating pedagogically requires recognizing the difficulties, challenges, and, above all, the intentionality of teaching. This is not restricted to the mere insertion of technological devices in the classroom. The discussions were firmly rooted in the work of numerous authors, with the main theoretical contribution coming from the work of: Jaume Carbonell, Isleide Fontenelle, Vani Moreira Kenski, Maria Isabel da Cunha, Francisco Imbernón, Laura H. Dalla Zen, Ana Cristina H. Ghisleni and Eliane Schlemmer. The research has resulted in the development of a kit comprising an e-book and collectible cards. This kit aims to mobilize new ways of teaching, learning, and producing knowledge in face-to-face education scenarios.
Keywords: Inovação pedagógica; Tecnologias digitais; Objetos Digitais de Aprendizagem; Educação profissional; Pedagogical innovation; Digital technologies; Digital Learning Objects; Professional education; ACCNPQ::Ciências Humanas::Educação